Anemia, mild cognitive impairment, and dementia among rural‐dwelling older adults: A population‐based study: Epidemiology / Prevalence, incidence, and outcomes of MCI and dementia. (7th December 2020) - Jiang, Ziying; Han, Xiaolei; Wang, Yongxiang; Hou, Tingting; Cong, Lin; Tang, Shi; Qiu, Chengxuan; Du, Yifeng
Abstract: Background: Evidence has emerged that anemia is associated with cognitive impairment and dementia in older people. However, their relationship has been rarely examined among people in low‐ and middle‐income countries. We aimed to investigate the associations of anemia and hemoglobin with mild cognitive impairment (MCI) and dementia among rural‐dwelling Chinese older adults. Method: This population‐based cross‐sectional study included 4, 838 participants (age ≥65 years; 57.0% women) who were living in the rural communities in western Shandong Province. Data on demographics, lifestyle, clinical conditions, and cognitive function were collected through face‐to‐face interviews, physical examinations, and laboratory tests. Anemia was defined as hemoglobin levels <13 g/dl in men and <12 g/dl in women. Cognitive function was evaluated using the Mini‐Mental State Examination (MMSE) and neuropsychological test battery. We defined MCI using Petersen's criteria and dementia according to the DSM‐IV criteria. Data were analyzed using multiple multinomial logistic and general linear regression models. Results: The overall prevalence of anemia was 20.1%, with the prevalence in people with normal cognition, MCI, and dementia being 19.2%, 22.8%, and 26.3%, respectively. Anemia was associated with a multiple‐adjusted odds ratio of 1.28 (95% CI: 1.04‐1.57) for MCI and 1.27 (95% CI: 0.87‐1.85) for dementia, and a multiple‐adjusted β‐coefficient of ‐0.60 (95% CI: ‐0.94 to ‐0.27) for MMSE score. Furthermore, a higher hemoglobin level was significantly associated with a greater C‐MMSE score ( P for trend <0.001), but not with dementia. Conclusions: Anemia is associated with MCI and poor global cognitive performance, but not with dementia among rural‐dwelling Chinese older adults. Furthermore, a higher hemoglobin level is correlated with better cognitive performance.